Medical controls in sports (analysis and results) - Xujabekov Akhror Ubaydullayevich (Zien Journals, 2022)
The effectiveness of sports training would be the highest if you will be using physical exercises together with training procedures, to comply with hygienic conditions, the mode for proper nutrition
Keywords: Self-control; medical control; educational control; functional state of the organism